Optimalisasi Fitur WhatsApp Business dalam Meningkatkan Efektivitas Promosi dan Penjualan pada UMKM di Era Digital - Novia, Siti Arita; Nazhirah, Afra; Wulandari, Nindya; Fani, Lastri Anggi (Jurnal Pengabdian West Science, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, including culinary businesses such as Warung Bakso Solo in Tanjung Pinang. However, in facing the digital era, Warung Bakso Solo still relies on conventional marketing strategies that have limitations. Through this community service program, an analysis of marketing needs and the implementation of WhatsApp Business as a relevant and easy-to-implement digital solution was carried out. WhatsApp Business helps improve communication with customers, facilitates promotions, and expands market reach through features such as product catalogs, automatic messages, and customer labels. The results of the community service show that the use of WhatsApp Business has a positive impact on increasing promotional effectiveness, operational efficiency, and strengthening relationships with customers. This program is expected to be the first step for other culinary MSMEs in utilizing digital technology to increase competitiveness and support business growth.